Assessing the Prevalence and Seroprevalence of Acute Dengue and Chikungunya Virus Infections from Theni, Tamil Nadu, India: A Retrospective Hospital-Based Study - Gopinath, R.; Arundadhi, M.; Dhanasezhian, A.; Sowndarya, M.; Daya Pauline S.; Thangam, G. Sucila (Medical Research and Its Applications Vol. 1, 2024)
The purpose of this study was to assess the prevalence and seroprevalence of acute dengue and chikungunya virus infections, as well as their co-infections. Viral-borne diseases have recently gained significant public health importance in the current world. Chikungunya disease has been documented in non-endemic countries, despite the fact that CHIKV has largely been detected in underdeveloped countries, suggesting the possibility of ongoing transmission to new locations. The Viral Research and Diagnostic Laboratory (VRDL) located at Government Theni Medical College (GTMC), Theni, Tamil Nadu conducts the diagnosis of common virus infections. The present study was a retrospective study conducted at the Viral Research and Diagnostics Laboratory (VRDL) located at a tertiary care hospital, in Theni, India from January 2018 to June 2023. DENV and CHIKV were detected using an enzyme-linked immunosorbent assay (ELISA) in all of the samples. This study included 16,997 cases, with 11264/2971 (26.3%) testing positive for Dengue IgM, 1395/288 (20.6%) for Dengue NS1 Ag, 19/3 (15.7%) for IgG, and 4319/3388 (8.9%) for CHIKV IgM. Fever (n = 16598, 97.6%) was the most prevalent clinical characteristic in all probable dengue and chikungunya patients. Other symptoms were chills (n = 11252, 66.1%), arthralgia (n = 10245, 60.2%), headache (n = 11354, 66.8%), and joint pain (n = 11256, 66.2%). The results demonstrated a lower probability of obtaining both DENV and CHIKV infections at the same time, although the risk is still not negligible. This study looks into the clinical appearance of suspected Dengue-Chikungunya patients. The increased frequency of Dengue and Chikungunya, as well as their co-infection, demands close monitoring of endemic regions and effective patient care management. Understanding the prevalence of Dengue-Chikungunya infection in this area will be easier with a longer time horizon, a larger sample size, and information on the co-infection status. Taking all of these aspects into account, prompt and effective treatment can aid in the prediction and control of viral epidemics.